Handbook of public economics - Auerbach, Alan J.; Feldstein, Martin S. (Amsterdam ; New York : Elsevier, 2002)
The field of Public Economics has been changing rapidly in recent years, and the sixteen chapters contained in this Handbook survey many of the new developments. As a field, Public Economics is defined by its objectives rather than its techniques, and much of what is new is thw application of modern methods of economic theory and economics to problems that have been addressed by economists for over two hundred years.
Originally published: Amsterdam ; New York : North-Holland ; New York : Elsevier Science [distributor], 1985-1987. (Handbooks in economics ; 4)
Includes bibliographical references and indexes.
gau 22/05/14
Loans
Keywords: Finance, Public; Welfare economics; Economics - public